Pulmonary Vein Stenosis Mimicking Nonspecific Interstitial Pneumonia - Karthika R. Linga; Andras Khoor; Jonathan A. Phelan; Isabel Mira-Avendano (Case Reports in Pulmonology)
Pulmonary vein stenosis (PVS) is a known complication after catheter ablation of arrhythmias. Surprisingly, little information is available on its manifestations in the lung. We describe the case of a 39-year-old woman who presented from an outside hospital with worsening shortness of breath after catheter ablation of pulmonary veins for atrial fibrillation. After an initial diagnosis of pneumonia and its nonimprovement with antibiotics, a surgical lung biopsy was done and interpreted as nonspecific interstitial pneumonia (NSIP) with vascular changes consistent with pulmonary arterial hypertension. Later, she was admitted to our institution where a transthoracic echocardiogram (TTE) and subsequent computed tomography (CT) angiogram of the heart showed severe stenosis of all four pulmonary veins. The previous lung biopsy was rereviewed and reinterpreted as severe parenchymal congestion mimicking NSIP. Our case demonstrates that PVS is an underrecognized complication of catheter ablation, and increased awareness among both clinicians and pathologists is necessary to avoid misdiagnosis.